Pesantren students’ religious beliefs and attitudes toward learning English in Indonesia - As Sabiq, Agus Husein; Moh. Roqib; Siti Sarah; Ma'ruf, Amin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Some students in Indonesian Pesantren (Islamic Boarding School) reported negative attitudes toward English as lingua Franca due to their environmental background, socio-cultural awareness, and identities. However, there are limited studies conducted in investigating their religious beliefs as the basis of pesantren students' attitudes toward learning English. Thus, this study aimed to investigate Indonesian pesantren students' attitudes toward learning English based on their religious beliefs and practices. The survey method was addressed to 250 respondents from three pesantren in Central Java. The researchers used a close-ended questionnaire adapted from the Attitudes/motivation Test Battery and 12 items focusing on the students' religious beliefs toward English. Besides, semi-structured interviews were conducted to get a deep understanding. This research employed one-way ANOVA and revealed a significant difference of the students' educational background in the pesantren on the mean of L2 attitudes, F = (14.40), Sig. = .000. The qualitative analysis revealed that ethnoreligious background shaped the positive attitudes of pesantren students toward English. Although most English speakers were non-believers, the students believed that learning English does not indicate the equal faith of non-believers and threat their religious identity. Furthermore, the participants claimed that learning English is important and not forbidden by religious teaching. They also thought that learning English can be considered as a kind of worship depending on the learner's intention, such as for communicating Islamic values to non-believers, future education, and improving careers.